INTRODUCTION - Deasy Yunita Siregar; Zulio Diva Ananta; Khairur Rizky; Sahrul Al Ichsan; Hamdan Syukran Hasnan (Riset : Jurnal Ilmiah Multidisiplin Ilmu, 2025)
English plays a significant role in higher education, requiring university students to understand and use the language in both academic and daily contexts. During their studies, students are exposed to formal English through academic texts, presentations, and written assignments, while informal English is commonly used in everyday communication, social media, and digital content. This study aims to examine the level of university students’ understanding of formal and informal English and to identify factors influencing their comprehension. This research employed a descriptive quantitative approach involving 15 university students from various academic backgrounds. Data were collected through a questionnaire and an English comprehension test to measure students’ understanding, frequency of use, and difficulties related to both language varieties. The data were analyzed using descriptive statistical methods, including percentages and average scores. The results show that students generally have a better understanding of informal English than formal English. Informal English is perceived as easier due to frequent exposure and simpler structures, while formal English is considered more difficult because of complex grammar and academic vocabulary. Nevertheless, students recognize the importance of formal English for academic and professional purposes. The study concludes that balanced instruction in both formal and informal English is essential in higher education. Keywords: formal English, informal English, university students, language comprehension Abstrak Bahasa Inggris memainkan peran penting dalam pendidikan tinggi, mengharuskan mahasiswa universitas untuk memahami dan menggunakan bahasa tersebut dalam konteks akademik maupun sehari-hari. Selama studi mereka, mahasiswa terpapar pada bahasa Inggris formal melalui teks akademik, presentasi, dan tugas tertulis, sementara bahasa Inggris informal sering digunakan dalam komunikasi sehari-hari, media sosial, dan konten digital. Penelitian ini bertujuan untuk menganalisis tingkat pemahaman mahasiswa universitas terhadap bahasa Inggris formal dan informal serta mengidentifikasi faktor-faktor yang memengaruhi pemahaman mereka. Penelitian ini menggunakan pendekatan kuantitatif deskriptif yang melibatkan 15 mahasiswa dari berbagai latar belakang akademik. Data dikumpulkan melalui kuesioner dan tes pemahaman Bahasa Inggris untuk mengukur pemahaman, frekuensi penggunaan, dan kesulitan yang terkait dengan kedua variasi bahasa tersebut. Data dianalisis menggunakan metode statistik deskriptif, termasuk persentase dan skor rata-rata. Hasil menunjukkan bahwa mahasiswa umumnya memiliki pemahaman yang lebih baik terhadap bahasa Inggris informal dibandingkan bahasa Inggris formal. Bahasa Inggris informal dianggap lebih mudah karena paparan yang sering dan struktur yang lebih sederhana, sementara bahasa Inggris formal dianggap lebih sulit karena tata bahasa yang kompleks dan kosakata akademik. Namun, mahasiswa menyadari pentingnya bahasa Inggris formal untuk tujuan akademik dan profesional. Studi ini menyimpulkan bahwa pengajaran yang seimbang antara bahasa Inggris formal dan informal sangat penting dalam pendidikan tinggi. Kata kunci: Bahasa Inggris formal, Bahasa Inggris informal, mahasiswa universitas, pemahaman bahasa